Approaches to Improving the Quality of Construction Drawings from Owner’s Perspective - Gao, Zhili; Walters, Russell C; Jaselskis, Edward J; Wipf, Terry J (Journal of construction engineering and management, 2006)
Members of the construction project team (e.g., owner, designer, and contractor) have increasingly become more interested in and concerned about improving communications, coordination, and cooperation during the drawing and specification development process. The current use of black and white construction drawings is not the best tool to permit designers and contractors to communicate efficiently and accurately. This study examines methods to improve the quality of drawing clarity through the use of color drawings and other technologies. A survey was used to collect feedback from designers to better understand the current challenges faced and potential solutions. An analysis of the survey results revealed the best approaches in the construction industry to improve drawing readability, and includes: (1) Using colored drawings, (2) improving design details, (3) reviewing drawings and specifications for consistency, and (4) using more three-dimensional (3D) modeling techniques. An example is presented that compares the traditional two-dimensional black and white drawing of a bridge pier with a 3D gray-shaded drawing.